Study of the Quality of Biogeotextile Materials as Semi-Organic Mulch on Saline Land - Wijayanti, Fitri; Maroeto, Maroeto; Lestari, Safira Riska; fatiha, Chosa zahro; Sholikah, Dinna Hadi; Ramadhani, Winih Sekaringtyas (JOURNAL OF TROPICAL SOILS, 2025)
Degraded land affects almost all ecosystems and can harm the progress and quality of human life, so it needs attention. Saline soil is a land degradation with high salt content that causes toxic effects, increases root osmotic pressure, and inhibits plant growth. One solution is using organic mulch processed into biogeotextiles because it can provide solutions for erosion control and soil stabilization while minimizing negative impacts on the ecosystem. This research was conducted from May to August 2023 in the experimental garden of the Faculty of Agriculture UPN ‘Veteran’ East Java. This study used a group randomized design with one factor,  the type of geotextile material consisting of reed grass (RG), straw (ST), pandanus odorifer (PO), and sugarcane bagasse (SB). This research was conducted with a litterbox of 20x20 cm filled with 100 g of biogeotextile material. The results obtained show that pandanus odorifer biogeotextile material is the best biogeotextile material because it can last a long time on the soil surface, but can still be adequately mineralized, according to the results obtained, reducing the C/N ratio and C-Organic but increasing total nitrogen. Decomposition is closely related to the materials’ quality rather than external factors. The quality of the material, namely lignin, organic carbon, C/N ratio, and nitrogen, influences the decomposition process. Furthermore, this technology can be applied to improve soil productivity and to keep soil healthy.